An 8-Month History of Meningitis in an Extremely Low Birth Weight Infant? – Long-lasting Infection with Ureaplasma parvum - Glaser, K.; Wohlleben, M.; Speer, C. P. (Zeitschrift für Geburtshilfe und Neonatologie, 2015)
Introduction: Ureaplasma spp. have been implicated in the pathogenesis of both preterm labor and neonatal morbidity including pneumonia and sepsis and the development of chronic lung disease of prematurity. Data on Ureaplasma meningitis are limited and partly controversially discussed.Patient: We report the unique case of a 9-month-old infant with progressive internal hydrocephalus of unknown origin and developmental delay due to a history of>200 days of inflammation of the central nervous system. The female extremely low birth weight infant had been referred to our hospital for ventriculoperitoneal shunt implantation. She had been born at 26+3 weeks of gestation with a birth weight of 940 g. With the exception of a moderate respiratory distress syndrome, postnatal period had been reported uneventful. However, internal hydrocephalus had become manifest at 4 weeks of postnatal age. Intraventricular hemorrhage had not been documented by cranial ultrasound and magnetic resonance imaging. Cerebrospinal fluid (CSF) analysis had repetitively revealed pronounced inflammation reflected by pleocytosis (50–86 leukocytes/μL, 60% lymphocytes), CSF protein levels of 578–1 026 mg/dL and undetectable CSF glucose. Although suggesting bacterial meningitis, microbial diagnostics had not been indicative, and empirical antibiotics had not affected the CSF findings. On admission to our hospital, CSF analysis still documented significant inflammation (125 leukocytes/μL, CSF protein 565 mg/dL, CSF glucose<2 mg/dL).Results: Due to a prenatal history of cerclage, we initiated microbial diagnostics on Ureaplasma spp. and Mycoplasma hominis. U. parvum was detected in CSF by culture and PCR, no other pathogens were isolated. On intravenous treatment with chloramphenicol, CSF profile continuously normalized, and cultures and PCR became negative. Treatment was continued for 3 weeks, and the infant was discharged after uncomplicated ventriculoperitoneal shunt placement. During a 12-month observation period she has shown encouraging recovery.Conclusion: In preterm infants, in particular, internal hydrocephalus of unknown origin and sustained CSF inflammation are highly suggestive of Ureaplasma meningitis. Our case highlights that infection may escape detection if not explicitly considered, since microbial diagnosis requires complex media and PCR.
Keywords: neonatal meningitis; preterm infants; Ureaplasma parvum; internal hydrocephalus; CNS inflammation